Komunikasi Spiritual Dalam Pemertahanan Kesucian Pura Batu Bolong Sebagai Destinasi Wisata Hindu di Lombok - Prayitno, Joko; Harianti, Dwi (IAHN Gde Pudja Mataram, 2025)
Batu Bolong Temple in Lombok is a Hindu tourist destination that combines historical heritage with stunning beaches, serving as a primary place of worship and spiritual contemplation for the Hindu community. The increasing flow of tourists has created the potential for the profanation of sacred spaces through commercialization, behavioral shifts, and environmental pressures, thus demanding new communication practices to maintain the sanctity of the temple. This interpretive qualitative study aims to reveal the role of spiritual communication in preserving the holiness of Batu Bolong Temple as a Hindu tourist destination, involving stakeholders, managers, devotees, and business actors as key participants. Data were collected through participant observation, in-depth interviews, and document studies, and then analyzed using the Miles and Huberman interactive model. The research results show three main forms of spiritual communication: ritual symbolic communication, interpersonal communication based on the values of dharma and tat twam asi, and educational communication to tourists regarding the sacred–profane boundaries. These three forms create an effective non-formal social regulation mechanism in maintaining the sanctity of the temple amidst tourism pressures, while also producing a conceptual model of destination spiritual communication as a theoretical contribution to the development of Hindu spirituality-based tourism